(untitled) (Eurasian Journal of Ecology, 2018)
In 2015, the authors investigated and found two populations and 4 coenopopulations of Iris alberti in the Ile-Alatau State National Nature Park. In the article, the authors present the ecological-coenotical characteristics of plant communities with the participation of Iris alberti within the studied population and describe the characteristics of seed production of this species. There were determined the number of generative shoots per 1 square meter, counted and measured fruit on them, the number of seeds in them, and the size of the average weight of 1000 seeds. Analysis of the Iris alberti seed production in the investigated populations showed that the percentage of flowering and fructification of this species under the in situ conditions were 48 – 62%, slightly higher than the ex situ conditions (33,3-39,1%). The average number of seeds, in a single generative shoots were insignificant, only 45-91 pcs. According to conducted counts of fruit size, the number of seeds in them, the number of seeds on shoots and weight of 1000 seeds were higher in plants in the population 2, which is probably due to the more favorable ecological and cenotical conditions of this habitat. Key words: Iris alberti , seed production, population, cenopopulation